Grape seed proanthocyanidin improves lipopolysaccharide-induced myocardial toxicity in mice - Liu, Xianchu; Li, Sha; Chen, Ruyan; Li, Yue; Liu, Ming; Peng, Huan (Penerbit Universiti Kebangsaan Malaysia, 2021)
Lipopolysaccharide (LPS) is an important pathogenic factor for sepsis which results in cardiovascular diseases and even mortality. Proanthocyanidin, one of the main components in grape seed, has a wide range of biological activities in various diseases. The mouse model was established by intraperitoneal injection with LPS. Grape seed proanthocyanidin (GSP) was administered continuously for 8 days. Our results showed that pre-treatment of GSP dramatically ameliorated the level of creatine kinase (CK) and lactate dehydrogenase (LDH) to defend against LPS-induced myocardial toxicity (p<0.01). Moreover, pre-treatment of GSP significantly mitigated the expression of matrix metallopeptidase 2 (MMP-2) and matrix metallopeptidase 9 (MMP-9) to inhibit LPS-induced myocardial fibrosis (p<0.01). In addition, pre-treatment of GSP significantly increased superoxide dismutase (SOD) and catalase (CAT) activities to improve the level of malondialdehyde (MDA) and hydrogen peroxide (H2 O2 ) (p<0.01). Lastly, pre-treatment of GSP relieved tumor necrosis factor alpha (TNF-α) and interleukin 6 (IL-6) activities to prevent inflammatory responses (p<0.01).